Study on natural gas metering technology and pricing methods in China - Yunyun XIE; Yao SU; Pengtao LI; Fan ZHANG; Wenyao LIU; Jianwen GUO (You-qi chuyun)
ObjectiveAmid the ongoing growth in demand within China’s natural gas market and the increasing diversification of supply sources, the adoption of advanced metering technology and reasonable pricing methods is closely tied to the interests of the government, enterprises, and consumers. Therefore, there is an urgent need to promote reforms in natural gas metering and pricing methods. MethodsThis paper begins with a comparative analysis of natural gas metering technologies between China and other countries, focusing on four aspects: natural gas metering standard systems, metering equipment applications, metrological traceability systems, and custody transfer metering modes. The subsequent quantitative analysis examines the differences between different metering and pricing modes in natural gas trade, revealing their effects in practical applications. Finally, the paper presents a summary and provides a future outlook on the development of natural gas metering technology in China. ResultsChina has established a relatively comprehensive natural gas metering technology framework, which includes laws, regulations, and technical standards related to metering, the selection and application procedures of metering equipment, and metrological traceability technology. This framework provides a fundamental guarantee to meet the needs of China’s rapidly expanding natural gas industry, while also playing a crucial role in safeguarding national interests and public welfare. Energy-based metering more accurately reflects the economic value of natural gas, particularly in the trade of gas from different sources and with varying compositions, as it helps eliminate errors caused by differences in gas composition. With the rapid and high-quality development of China’s natural gas industry, the natural gas metering standard system is expected to undergo continuous improvement, the localization of metering equipment is anticipated to accelerate, and the metrological traceability technology is expected to be continuously upgraded for energy-based natural gas metering. Additionally, there will be a gradual transition from traditional volumetric metering to energy-based metering in custody transfer. ConclusionPromoting reforms in natural gas metering and pricing methods not only enhances resource utilization efficiency but also ensures market fairness and transparency. While China’s current natural gas metering technology framework largely meets the needs of the domestic natural gas industry, further enhancements and refinements are necessary to address the increasingly complex competition in the international natural gas market in the future.